2001
DOI: 10.1108/eum0000000005995
|View full text |Cite
|
Sign up to set email alerts
|

netLibrary: a new direction in collection development

Abstract: Texas A&M University (TAMU) Libraries is a member of two consortiums that include academic and public libraries. Both consortiums purchased access to netLibrary e‐books for their members. Approximately 92 libraries within the Amigos Library Services consortium jointly purchased roughly 10,000 e‐books. The Texas State Library and Archives Commission (TSLAC), which oversees a consortium of approximately 700 state‐supported libraries, purchased roughly 9,000 e‐books. TAMU purchased an additional 193 e‐books for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…For example, in terms of library e-book usage as it relates to subjects, researchers found that students and academics access e-books in some subjects more so than they do in other subjects. In an analysis of universities' e-book data usage, both Dillon (2001) and Ramirez and Gyeszly (2001) found that e-books were more popular in Computer Science, Economics, and Business than they were in other subject areas. The results were similar in a study conducted by Fernandez (2003).…”
Section: Introductionmentioning
confidence: 97%
“…For example, in terms of library e-book usage as it relates to subjects, researchers found that students and academics access e-books in some subjects more so than they do in other subjects. In an analysis of universities' e-book data usage, both Dillon (2001) and Ramirez and Gyeszly (2001) found that e-books were more popular in Computer Science, Economics, and Business than they were in other subject areas. The results were similar in a study conducted by Fernandez (2003).…”
Section: Introductionmentioning
confidence: 97%
“…Medicine consistently fell into the top ten subject areas using e-books (Langston, 2003, p. 26-27;Chan (2005, p. 214;Bailey, 2006, p. 58;Wilkins, 2007, p. 249). Despite this higher use of electronic books in certain subject areas, both Ramirez &Gyeszly (2001, p. 163) andFernandez (2003, p. 28-29) found an overall preference of print for all subject areas. Woo (2005) found that medicine preferred print to electronic at a rate of two-toone (p. 132).…”
Section: Introductionmentioning
confidence: 97%
“…As part of a larger collection development study, Ramirez and Gyeszly surveyed patrons (including undergraduates) to seek attitudes and preferences on electronic resources and found "that most patrons still favor the printed books over e-books." 17 Dilevko and Gottlieb examined undergraduates' use of print and online resources. Their study found that undergraduates associated use of printed books with more "high-quality work."…”
mentioning
confidence: 99%